Thin layer deposition of TiO2 and PMMA on optical micro or nano fibers for nonlinear optics - Divay Laurent; Eustache Etienne; Bouhadida Maha; Larat Christian; Azzoune Abderrahim; Beugnot Jean-Charles; Lebrun Sylvie (Journal of the European Optical Society-Rapid Publications)
Over the last twenty years, silica optical tapered micro or nanofibers (called ONF in the following) have been widely exploited for a large range of potential applications in several areas of research for their original properties of light propagation. The high confinement of the optical mode in the uniform part and the presence of a strong evanescent field near the surface make them devices of choice for nonlinear applications. In this paper we study the coating of ONF with nonlinear materials to expand further the possibilities offered by these devices. Two materials are chosen for the coatings, Titanium Dioxyde (TiO2) and Polymethyl Metacrylate (PMMA). Two processes have been developed for the coatings. Firstly, Atomic Layer Deposition has enabled to deposit controlled thin layers of TiO2 of several tens of nm on an ONF having a diameter of 1 μm with very low additional losses (0.5 dB). Secondly, we have realized a multiple layer deposition process to deposit PMMA layers on ONF. With this technique we were able to reach thicknesses of about 100 nm on ONF diameters as small as 1 μm. The encapsulation of a coated tapered fiber in silicone has been conducted, resulting in minimal additional losses, showing great promises from such a treatment. These initial experimental proofs of concept open the way for further experiments in nonlinear optics using functionalized ONF. Potential applications include the development of Raman converters within the evanescent field of the optical propagating mode, as well as experiments that necessitate precise control of phase matching.